(untitled) (Gestión y Gerencia, 2019)
The purpose of this essay was aimed to reflect about professional training from the axiological configuration of social responsibility in university management; for which a review of the theoretical aspects that explain some of the implications of the constructs related to an academic vision of classroom management was made, consistent with the teacher’s task beyond the instructional to facilitate the training of professionals required by the country to assume a proactive, critical and reflective attitude towards the search for awareness of socially responsible value. The axiology as a theory of value, in addition to the philosophical positioning, has an existential reference inherent to the professional training reflected in the behaviors demonstrated in the actions of citizen participation, solidarity and ethical behavior to assume the increasingly complex environments where economic, social and other problems prevent societies’ development. Thus, university social responsibility alludes to the consistent commitment to the training of future professionals and the ways in which they will work in companies from an ethical and responsible perspective that contributes to the common good and social justice. It was concluded from an axiological view, that values such as fraternity, solidarity, and social responsibility should guide the academic work aimed at achieving honest citizens committed to the society of which they are part of and to which they will turn their knowledge to improve their quality of life, trying to solve the problems that the knowledge society itself faces